Structural and Phase Transformation in a Cold-Deformed Titanium Alloy During Aging - Illarionov, A.G.; Narygina, I.V.; Karabanalov, M.S.; Kylosova, I.A. (KnE Engineering, 2019)
The change of structure, phase composition and properties during aging of VT22 (Ti-5Al-5Mo-5V-1Fe-1Cr) titanium alloy rods, pre-quenched from